Pengembangan Exchange Trade Fund Syariah Indonesia: Peluang dan Tantangan - Azmiana Risca; Rifqi Muhammad (ITB AAS INDONESIA Surakarta, 2021)
This paper aims to discuss the opportunities and challenges of developing Sharia Exchange Trade Fund (ETF) investment products in Indonesia. ETF is an investment product in the capital market that collaborates stock and mutual fund products that can collectively be traded on the capital market. This will provide attractive new investment opportunities for investors who are concerned about sharia investment. With the consideration that Indonesia's population is predominantly Muslim, then of course Islamic investment products will attract them. ETFs have the following advantages: easy and flexible process of ownership and transfer, low cost and risk, wide coverage because they are like investing in several portfolios at once, and the process is transparent. In particular, Islamic ETFs have the advantage in the aspect of ensuring product halalness because their portfolios are always monitored by the sharia supervisory board in each investment manager as the manager. On the other hand, Islamic ETFs are faced with challenges related to the low literacy of the Muslim community about investing in the capital market that has sharia products.